2022
DOI: 10.1002/dvdy.480
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 expression and function in mammalian cochlear development

Abstract: Background: PR domain containing 16 (PRDM16) is a key transcriptional regulator in the development of craniofacial, adipose, and neural tissues. Our lab identified PRDM16 expression in the epithelial cells of the Kölliker's organ (KO) that starts at ~E13.5 and is maintained until KO disappearance. A transgenic mouse model that carries a gene trap null allele of Prdm16 (Prdm16 cGT ) was used to characterize the impact of Prdm16 loss on cochlear development.Results: At P0 Prdm16 cGT null cochlea exhibited hypopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Prdm16 null mutant mice showed phenotypes similar to those of Ebf1-deleted mice, including shortened cochlear length, spiral limbus loss, and ectopic hair cells within the GER. Moreover, the Prdm16 null mutant mouse cochlear duct expressed approximately half the amount of Ebf1 compared to the wild-type mouse cochlear duct (Ebeid et al, 2022), suggesting that EBF1 is involved in the development of Kölliker's organ. However, if PRDM16 is the direct upstream regulator of EBF1, the Ebf1 expression level should be much less in Prdm16 null mutant mice, and these mice should exhibit increased hair and supporting cells and loss of scala tympani, as observed in Ebf1 -/-mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prdm16 null mutant mice showed phenotypes similar to those of Ebf1-deleted mice, including shortened cochlear length, spiral limbus loss, and ectopic hair cells within the GER. Moreover, the Prdm16 null mutant mouse cochlear duct expressed approximately half the amount of Ebf1 compared to the wild-type mouse cochlear duct (Ebeid et al, 2022), suggesting that EBF1 is involved in the development of Kölliker's organ. However, if PRDM16 is the direct upstream regulator of EBF1, the Ebf1 expression level should be much less in Prdm16 null mutant mice, and these mice should exhibit increased hair and supporting cells and loss of scala tympani, as observed in Ebf1 -/-mice.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, PRDM16 was reported to be a marker of Kölliker's organ and an important molecule in its development (Ebeid et al, 2022). Prdm16 null mutant mice showed phenotypes similar to those of Ebf1-deleted mice, including shortened cochlear length, spiral limbus loss, and ectopic hair cells within the GER.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that PRDM16 is highly expressed in the nuclei of Kölliker’s organ-supporting cells in the bottom and middle cochlear apex by embryonic day 13.5 and decreases rapidly at birth. Its expression in the Kölliker’s organ continued throughout development until postnatal day 7, and PRDM16 was thus suggested as a possible specific marker for Kölliker’s organ-supporting cells (Ebeid et al, 2022 ). Further, by studying the model with Prdm16cGT double allele deletion mice, it was found that the cochlear Kölliker’s organ of Prdm16 gene-deficient mice at day P0 had poor development, shortened cochlear ducts, reduced proliferation of Kölliker’s organ-supporting cells, increased density of hair cells and supporting cells in the parietal ring, and loss of anchoring ability of the lid membrane to the Kölliker’s organ, indicating that Prdm16 is a regulatory gene necessary for Kölliker’s organ-supporting cells’ proliferation (Ebeid et al, 2022 ).…”
Section: Biological Functions Of Kölliker’s Organ-supporting Cells In...mentioning
confidence: 99%
“…Its expression in the Kölliker’s organ continued throughout development until postnatal day 7, and PRDM16 was thus suggested as a possible specific marker for Kölliker’s organ-supporting cells (Ebeid et al, 2022 ). Further, by studying the model with Prdm16cGT double allele deletion mice, it was found that the cochlear Kölliker’s organ of Prdm16 gene-deficient mice at day P0 had poor development, shortened cochlear ducts, reduced proliferation of Kölliker’s organ-supporting cells, increased density of hair cells and supporting cells in the parietal ring, and loss of anchoring ability of the lid membrane to the Kölliker’s organ, indicating that Prdm16 is a regulatory gene necessary for Kölliker’s organ-supporting cells’ proliferation (Ebeid et al, 2022 ). Cochlear duct development requires the proliferation of these cells for convergent extension and to achieve normal hair cells and supporting cell densities within the organ of Corti (Chen et al, 2002 ; Driver et al, 2017 ).…”
Section: Biological Functions Of Kölliker’s Organ-supporting Cells In...mentioning
confidence: 99%